Pengelolaan dan Pemasaran Ganyong sebagai Salah Satu Potensi Pertanian Desa Terbah untuk Mengembangkan Kuliner Yogyakarta - Sitepu, Roberto (Jurnal Atma Inovasia, 2023)
Counseling activities were carried out from April to May 2022 with the Society 5.0 method where this espionage activity was carried out by not sending students to the field. The implementation of unit B was placed in Terbah Village, Patuk District, Gunungkidul Regency, Special Region of Yogyakarta. In this program, there will be counseling related to the management and marketing of canna which can be a potential to develop Yogyakarta’s culinary. The programs implemented by unit B are Village Potential Extension and Guidebook Making. The results of the counseling include (1) E-books and documentation of the development of Terbah Village Potential as a tourist spot; (2) E-books and documentation of the potential development of Terbah Village as a culinary place for canna tubers.